Evaluation of Inclusive and Multicultural Education Policies to Support the Achievement of the Sustainable Development Goals (SDGs) at Tumbuh Elementary School in Yogyakarta - Era Mutiara; Suranto Aw; Mawaddah Fatin Nuradiah; Isti Faniyah; Nur Khafifah Luthfiyah B; Bernadeta Elsa Gita Saputri (Journal of Educational Sciences, 2026)
This study was motivated by the need for empirical evidence on the effectiveness of inclusive and multicultural education policies at the elementary school level to ensure fairness and the quality of learning. The purpose of this study was to evaluate the inclusive and multicultural education policies at SD Tumbuh Yogyakarta in support of the Sustainable Development Goals (SDGs). This evaluative study employs the CIPP (Context, Input, Process, Product) model within a mixed-methods, concurrent embedded design. Data were collected through document studies, in-depth interviews, and questionnaires that adapted the Index for Inclusion and multicultural education indicators. The evaluation results show positive achievements in all components. The Context component for inclusive education achieved a rating of “Very Good” (81%), while the multicultural component achieved a rating of “Good” (61%). In the Input component, the availability of infrastructure for inclusive and multicultural education was also adequate. The Process component of learning achieved a “Very Good” rating (87.50%), and the Product component showed positive social and academic development in students, supported by a flexible assessment system. Overall, the inclusive and multicultural education policies at SD Tumbuh have been well implemented and have contributed to creating a fair, high-quality learning environment that supports the SDGs, although there is still a need to strengthen aspects of multiculturalism and parent involvement.